2009
DOI: 10.1177/1545968309336148
|View full text |Cite
|
Sign up to set email alerts
|

Is Visuospatial Hemineglect Longitudinally Associated with Postural Imbalance in the Postacute Phase of Stroke?

Abstract: Visuospatial hemineglect is an independent covariate that is longitudinally associated with postural imbalance after stroke. These findings suggest that hemineglect is an important factor for controlling static and dynamic standing balance during the first months poststroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…Neglect is primarily associated with the right hemisphere and there is a wealth of evidence also demonstrating the dominance of the right hemisphere for control of balance and posture (Bohannon, Smith, & Larkin, 1986;Malhotra, Coulthard, & Husain, 2006;Perennou, 2006;Punt & Riddoch, 2002;Spinazzola, Cubelli, & Della, 2003;Taylor, Ashburn, & Ward, 1994). A longitudinal association between neglect and poor postural control during the first three months after stroke has also recently been established, highlighting the apparent importance of the deficit in regaining balance (van Nes et al, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Neglect is primarily associated with the right hemisphere and there is a wealth of evidence also demonstrating the dominance of the right hemisphere for control of balance and posture (Bohannon, Smith, & Larkin, 1986;Malhotra, Coulthard, & Husain, 2006;Perennou, 2006;Punt & Riddoch, 2002;Spinazzola, Cubelli, & Della, 2003;Taylor, Ashburn, & Ward, 1994). A longitudinal association between neglect and poor postural control during the first three months after stroke has also recently been established, highlighting the apparent importance of the deficit in regaining balance (van Nes et al, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have found that unilateral spatial neglect independently affected trunk balance in stroke patients 6. Other studies also found that unilateral spatial neglect affected trunk balance six to twelve weeks after stroke occurrence 7. In addition, unilateral spatial neglect hampers effects of rehabilitation treatments and slows down functional recovery.…”
Section: Introductionmentioning
confidence: 97%
“…The presence of hemineglect is associated with postural control after stroke [15]. Kerhoff et al [1] pointed out that trunk rotation toward the neglect side reduces neglect manifestation, and head-trunk compensation may improve the patient’s performance in the line bisection test.…”
Section: Discussionmentioning
confidence: 99%
“…Severe impairment of functional activities of daily living (ADLs) has been found in patients with large right hemisphere lesions [3,4]. Patients with hemineglect have been reported to show lower recovery of ADLs [5,6,7,8,9,10], poorer posture control [11,12,13,14,15], greater hemiparesis [16], increased risk of falling [17,18], and worse functional outcome [19] than those without hemineglect. Therefore, it is important for clinicians to identify and analyze the severity of hemineglect in stroke patients and alter the rehabilitation program accordingly to reduce the severity of hemineglect [1,20,21,22] and improve the functional outcome [19,23].…”
Section: Introductionmentioning
confidence: 99%